(untitled) (Journal of Partial Differential Equations, 2020)
This paper is concerned with the pullback dynamics of 2D non-autonomous Navier-Stokes-Voigt equations with continuous and distributed delays on bounded domain. Under some regular assumptions on initial and delay data, the existence of evolutionary process and the family of pullback attractors for this fluid flow model with Klein-Voight damping are derived. The regular assumption of external force is less than [1].